PENGGUNAAN MEDIA PEMBELAJARAN BAHASA INGGRIS DI SD YPK YOKA BARU KOTA JAYAPURA, PAPUA - Budi Rahayu; Wigati Yektiningtyas (LPPM Uncen, 2018)
Teaching English as a foreign language in Indonesia is challenging. The purpose of this program is to overcome several of the many challenges in teaching English, that is the use of teaching media. Conducted in SD YPPK Yoka Baru, Jayapura, the method used is participation which involves students from English Department, FKIP Uncen. The activities include preparing, designing, and demonstating the teaching media. The result shows that using teaching media is effective to improve the students’ motivation in learning English.Keywords: teaching english, the teaching media, student, Jayapura